New mechanism for glomerular injury. Myeloperoxidase-hydrogen peroxide-halide system. - Johnson, R J (1987)
Reactive oxygen species, particularly hydrogen peroxide (H2O2), participate in neutrophil-mediated glomerulonephritis. However, the mechanism of H2O2 neptrotoxicity is unknown. Myeloperoxidase (MPO), a neutrophil cationic enzyme that localizes in glomeruli, can react with H2O2 and halides to form highly reactive products. We tested the hypothesis that the MPO-H2O2-halide system may induce glomerular injury by infusing MPO followed by H2O2 in a chloride-containing solution into the renal artery of rats. Controls received MPO or H2O2 alone. MPO-H2O2-perfused rats developed significant proteinuria, endothelial cell swelling, and epithelial cell foot process effacement, whereas control kidneys were normal. In the presence of free 125I, MPO-H2O2-perfused rats incorporated large amounts of 125I, localized to the glomerular basement membrane and mesangium by autoradiography, into glomeruli. Glomerular iodination was greatly decreased or absent in controls. The MPO-H2O2-halide system causes glomerular injury and may be important in neutrophil-mediated glomerulonephritis.